The Great. Season two [videorecording (DVD)] - Fanning, Elle, 1998-; Hoult, Nicholas, 1989-; Fox, Phoebe, 1987-; Dhawan, Sacha, 1984-; Wakefield, Charity, 1981-; Lee, Gwilym, 1983-; Godley, Adam; Hodge, Douglas; Bromilow, Belinda, 1975-; Gbadamosi, Bayo; Keith-Roach, Florence; Samal, Danusia; et al. (Paramount Home Entertainment, 2022)
The Great returns in Season Two from Golden Globe and Academy Award nominee Tony McNamara (The Favourite). Catherine finally takes the Russian throne for her own- but if she thought coup-ing her husband was difficult, it's nothing compared to the realities of liberating a country that doesn't want to be. She'll battle her court, her team, even her own mother in a bid to bring the Enlightenment to Russia.